How community therapists describe adapting evidence‐based practices in sessions for youth: Augmenting to improve fit and reach. Issue 4 (25th February 2020) - Kim, Joanna J.; Brookman‐Frazee, Lauren; Barnett, Miya L.; Tran, Melanie; Kuckertz, Mary; Yu, Stephanie; Lau, Anna S.
Abstract: The study sought to (a) characterize the types and frequency of session‐level adaptations made to multiple evidence‐based practices (EBPs) and (b) identify therapist‐, client‐, and session‐level predictors of adaptations. Within the community implementation of multiple EBPs, 103 community mental health therapists reported on 731 therapy sessions for 280 clients. Therapists indicated whether they adapted EBPs in specific sessions and described adaptations in open‐ended responses. Responses were coded using the Augmenting and Reducing adaptations framework. Therapists reported making adaptations in 59% of sessions. Augmenting adaptations were reported more frequently than Reducing adaptations. Multilevel logistic regression analyses revealed that greater therapist openness to EBPs, younger child age, and presenting problems was associated with Augmenting adaptations. Child presenting problem of externalizing problems predicted fewer Reducing adaptations compared with internalizing problems. This study extends the growing research examining adaptations within the context of the system‐driven implementation of multiple EBPs by applying the Augmenting and Reducing adaptation framework to the session‐level.